THE DEVELOPMENT AUTHORITY IMPLEMENTATION OF JUDICIAL REVIEW BY THE CONSTITUTIONAL COURT OF THE REPUBLIC OF INDONESIA - Siallagan, Haposan (SCAD Independent, 2017)
All typical products regulated the state could be reviewed and tested through legal actions (legal remedies) facilitated by the constitution of the Republic of Indonesia. This mechanism has known as a review action. In addition, the review on the legislation, related to authorization or the right to review it (toetsingsrecht or the right to review) could be consisted of judges and executives and also the legislatives. The authority of judicial review by the constitutional court is a judicial authority of the constitution. The authorization was a result of the third amendment to the Indonesian constitution of 1945. Regarding the developments of the implementation of the judicial authority by the constitutional court, there were increasing trend of judicial reviews year to year. Thus it indicates the number of regulations have problematic issue in term of of quality. Therefore, it is very urgent to critically evaluate the quality of the formulation of laws in order to avoid the cancellation of the law itself through a judicial authority possessed through the constitutional court.